Inhibitory Effect of Gallic acid on Production of Interleukins in Mouse Macrophage Stimulated by Lipopolysaccharide - Wansu Park (Korean Pharmacopuncture Institute, 2010)
Objectives: Gallic acid (GA) is the major component of tannin which could be easily founded in various natural materials such as green tea, red tea, grape juice, and Corni Fructus. The purpose of this study is to investigate the effect of Gallic acid (GA) on production of interleukin (IL) in mouse macrophage Raw 264.7 cells stimulated by lipopolysaccharide (LPS). Methods: Productions of interleukins were measured by High-throughput Multiplex Bead based Assay with Bio-plex Suspension Array System based on xMAP􄠶 (multi-analyte profiling beads) technology. Firstly, cell culture supernatant was obtained after treatment with LPS and GA for 24 hour. Then, it was incubated with the antibody-conjugated beads for 30 minutes. And detection antibody was added and incubated for 30 minutes. And Strepavidin-conjugated Phycoerythrin (SAPE) was added. After incubation for 30 minutes, the level of SAPE fluorescence was analyzed on Bio-plex Suspension Array System and concentration of interleukin was determined. Results: The results of the experiment are as follows. 1. GA significantly inhibited the production of IL-3, IL-10, IL-12p40, and IL-17 in LPS-induced mouse macrophage RAW 264.7 cells at the concentration of 25, 50, 100, 200 uM (p<0.05). 2. GA significantly inhibited the production of IL-6 in LPS-induced mouse macrophage RAW 264.7 cells at the concentration of 50, 100, 200 uM (p<0.05). 3. GA diminished the production of some cytokine such as IL-4, IL-5, and IL-13 in LPS-induced mouse macrophage RAW 264.7 cells. 4. GA did not show the inhibitory effect on the production of IL-1αand IL-9 in LPS-induced mouse macrophage RAW 264.7 cells. Conclusions: These results suggest that GA has anti-inflammatory activity related with its inhibitory effects on the production of interleukins such as IL-3, IL-10, IL-12p40, IL-17, and IL-6 in LPS-induced macrophages.